Investigation of Urban Transformation Process, Methods, and Techniques: Elazig Province Sample - Elyiğit, Belkıs; Ekinci, Cevdet Emin (My University, 2024)
This study aims to examine and present the general results of the urban transformation studies methods and techniques applied in the province of Elazig after the Sivrice earthquake. The study used a descriptive approach method within the scope of qualitative research. Urban transformation project data applied in risky areas were obtained from technical analysis and interviews. The research covers the results of urban transformation in risky areas of Elazig province. Cleaning, renewal, and post-disaster transformation methods were used in urban transformation works in risky areas. The general situation after the earthquake has revealed some weaknesses in selecting methods and techniques for urban transformation applications. As a result of urban transformation practices, bioharmological buildings that are more compatible with the current earthquake legislation, with a stronger carrier system, more comfortable, and in terms of user identity and purpose of use, are offered to the use of beneficiaries.
Keywords: Urban Transformation; Urbanization; Elazig; Urban Transformation Process; Risky Area